Prolonged hormonal contraception: current research and practice: A review - Natalia V. Aganezova; Sergey S. Aganezov (IP Berlin A.V., 2022)
This review presents information on demographic processes in Russia and the relevance of highly effective contraception for the prevention of artificial abortion. We present data on the etonogestrel implant (68 mg), an innovative single-stranded subcutaneous implant, a long-acting reversible contraceptive option with high efficacy (Pearl index 0.05) with optimal and typical use of the product. We analyzed the results of the studies that showed a favorable safety profile of the etonogestrel implant with no significant effect on the risks of thrombotic events, metabolic processes, depression incidence, bone mineral density, and characteristics of reproductive function after discontinuation of the drug. The article presents data on possible side effects in the form of changes in the characteristics of menstrual bleeding and a slight increase in body weight, which is comparable with the natural gain in an adult with age. The importance of qualified counseling of patients before and during the use of etonogestrel implants is emphasized.